Depression and anxiety in greek male veterans after retirement - Kypraiou, Aspa; Sarafis, Pavlos; Tsounis, Andreas; Bitsi, Georgia; Andreanides, Elias; Constantinidis, Theodoros C.; Kotrotsiou, Evaggelia; Malliarou, Maria (My University, 2017)
Introduction: Retirement is a turning point in human life, resulting in changes to physical and mental health status. The aim of this study was to examine the factors that are related with depression and anxiety symptoms in Greek male veterans after retirement. Materials and Methods: A total of 502 veterans participated in a cross-sectional study. Beck Depression Inventory for depression assessment and Spielberger Trait Anxiety Inventory for anxiety assessment were used. The Ethics Committee of the Technological Educational Institution of Thessaly granted permission for conducting the research, and informed consent was obtained from all the participants. Questionnaires were filled in electronically using a platform that was made for the specific research. Mean values, standard deviations, Student t test, nonparametric cluster analysis of variance, Pearson’s and Spearman’s coefficients, and linear regression were conducted, using the Statistical Program for Social Services version 19.0. Results: Severe depression was found in 3.8% of veterans with a mean score of 6.78, whereas 23.2% displayed mild-to-moderate symptoms of depression. Mean score of state anxiety was found to be 36.55 and of trait anxiety 33.60. Veterans who were discharged because of stressful working conditions, those who have a high body mass index, consume regularly alcohol, smoke and were not satisfied by changes in their everyday life after retirement had significantly more symptoms of depression and anxiety, although those who retired because of family problems had significantly more symptoms of depression. Multivariate linear regression analyses indicated that dissatisfaction related to lifestyle changes had statistically significant effect on symptoms of depression and anxiety, and stressful working conditions as a leading cause for retirement had statistically significant effect on depression. Finally, according to linear regression analyses results, those who were satisfied with their professional evolution had 1.80 times lower score in depression scale. Conclusion: The sense of satisfaction derived from fulfilling work-related expectations when finishing a career, with changes in everyday life, and smoking and alcohol reduction, may contribute to a better adjustment during the retirement period. To our knowledge, this was the first study examining depression and anxiety levels in Greek veterans, and the sample size was large, covering a randomly chosen veteran population. On the other, it was a convenient sample, although the study results could not focus on direct-term effects of retirement (up to 3 years of retirement from active service). Primitive data may be used for research directions in the future.
Keywords: Retirement; Depression; Anxiety; Veterans; Greek male